Sobre uma classe especial de grupos nilpotentes - Claudiano Henrique da Cunha Melo (2015)
Finite p-groups form a particular class of nilpotent groups and are very important objects in group theory. In this work, we present classical results from the finite p- groups theory and some results of classication such as a simple classication of the groups of order p4 using the concept of extension types.